Serum biochemistry and liver histology of female rabbits fed white mangrove (Langucularia racemosa) leaves as feed additive - A. Yahaya, Mohammed; N. Wekhe, Samuel; Akinola, A. F. (Journal of Advanced Veterinary and Animal Research, 2015)
This study was conducted to assess the effect of white mangrove (Langucularia racemosa) leaves (as feed additive) on some serum biochemistry in adult female rabbits. Twenty four mature female rabbits (does) were randomly allocated to four equal groups (Group A, B, C, and D) in a Randomized Complete Block Design (RCBD). Group A was served with control diet, while the does of Group B, C and D were fed growers mash mixed with the additive dosed at 70 g, 80 g, and 90 g/kg of feed, respectively. Blood samples were collected from the animals for biochemical analysis at the end of the 12-week study. Sections of the liver were collected from same does for histological investigations. The results of the serum biochemistry showed no significant difference (p>0.05) in the values of Aspartate Transaminase (AST), while significant differences (p<0.05) were observed in the values of Alanine Transaminase (ALT), and Alkaline phosphatase (ALP). The histology of the liver was normal. It was concluded that the test ingredient (L. racemosa) was safe to be used in the diet of female rabbit dosed at 70-90g/kg feed since the enzyme levels remained within normal range of healthy rabbit. http://dx.doi.org/10.5455/javar.2015.b63